Leadership in Learning Organization of Islamic Boarding School After Covid-19 Pandemic - Muhammad Anggung Manumanoso Prasetyo; Muhammad Ilham (Pascasarjana Pendidikan Agama Islam Institut KH. Abdul Chalim Mojokerto, 2022)
This article aims at providing an institutional landscape analysis resting on aspects of leadership as a boarding school education policy amid the Covid-19 pandemic. The study is carried out qualitatively using analysis survey methods. Data is critically analyzed through various relevant literature. Data analysis was reinforced by the results of interviews on boarding school leadership in Aceh. The results of the study found the conceptual framework of the effectiveness of boarding school leadership in facing pandemic situations. The politics of leadership policy consist of four organizational areas that were usually arenas of policy-making, namely structural change, inter-departmental coordination, success management and resource allocation. Whereas the learner organizational leadership strategy namely (1) the readiness of long-term program blueprint; (2) the degree of focus in building, caring and developing a work mechanism; (3) the experience of the Boarding Board in executing financial strategies refers to less optimal field operational aspects due to pandemic; (4) strengthening partnership-based cooperation networks accompanied by systemic evaluation of the implementation of boarding school education and teaching and to oversee how the consequences system work in the middle of a covid-19 pandemic. The expected implications can extend the conceptual insight of effective leadership and the politics of education policy in general.